PENGARUH IMPLEMENTASI SISTEM MANAJEMEN DAERAH (SIMDA), KUALITAS SUMBER DAYA MANUSIA DAN PENERAPAN STANDAR AKUNTANSI PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN MALANG - Listiya Ayuningsih; M. Cholid Mawardi; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
The purpose of this study was to determine the effect of the implementation of SIMDA (Regional Management Information System), human resources and the application of government accounting standards on the quality of financial reports in the Malang Regency. Sanusi (2014) population is the entire collection of elements that show certain characteristics that can be used to make a collection. The set of elements shows the number of , while certain characteristics indicate the characteristics of the group. In practice, a researcher rarely conducts research on the entire set of elements (population). The element is the subject on which the measurement is made. . The population in this study were employees of BKAD (regional financial and asset agency) Malang regency. The results of this study indicate that the effect of simda implementation, human resources and the application of government accounting standards has a positive and significant effect on the quality of the local government's financial reports in Malang Regency.Keywords : SIMDA, Human Resources, Application of Accounting Standards.